New Paradigms in Trauma Care – an analysis of a trauma centre registry - Gomes, Ernestina (2010)
RATIONAL Trauma is a leading cause of burden worldwide namely in young and healthy people. Portugal, mainly in relation to the road traffic collision number, has a particular problem. Despite its epidemiologic relevance there is a lack of data to allow a reliable characterization of the problem, namely in terms of severity and outcome. When addressing the care of trauma patients there are current paradigms like the trimodal mortality and the golden hour, that are not only linked but are also the basis for the design of most of the trauma systems in the world. However the controversy about the best model for the care of trauma patients in the pre-hospital environment goes on with the scoop and run model (also known as BLS and based on the described paradigms) competing with the stay and play model (also known as ALS). It has been emphasised that to find benefit with ALS in pre-hospital one must find the specific trauma population that will maximise and profit from ALS. AIMS The aims of this thesis are to discuss the trimodal mortality and the golden hour current concepts and to raise new paradigms in the sense of original and innovative perspectives and implications for the care of trauma patients. RESEARCH QUESTIONS The thesis addresses 5 research questions. 1. Is the trimodal mortality pattern applicable in a Portuguese Trauma System? 2. Is time to definitive treatment at trauma centre an independent factor contributing to mortality? 3. Does the early treatment of life threatening events have implications for trauma mortality? 4. Does rurality have implications on trauma patient’s outcome? 5. Does the early treatment of life threatening events have negative implications on disability and quality of life of trauma survivors? METHODS This study is based geographically and operationally in the HGSA trauma system involving a catchment area of about 2 million habitants in the north of Portugal. The study that is the basis for this thesis was deve-loped since 2001 in three different and continuous phases. First, in 2001, a trauma registry was developed in HGSA, the trauma centre for severe trauma patients in the trauma system. Then a population based study was performed in all the trauma system area to study only trauma deaths. The trauma registry includes patient, pre-hospital, first hospital and trauma centre variables. Severity coding was done using TRISS methodology. Finally in 2003 the follow-up clinic was built and the trauma patient disability and quality of life assessment started. The studied exposure and outcomes were: place of treatment of life threatening events, time to trauma centre, rurality, mortality (in-hospital and after discharge), disability and quality of life at 6 months. MAIN FINDINGS AND THE NEW PARADIGMS: 1. Mortality distribution in our trauma system has a Tetramodal pattern. 2. A Golden Approach – treating life threatening events prior to transfer to trauma centre – is more important to decrease mortality than a golden hour. 3. Treating life threatening events early in the pre-hospital setting (pre-hospital ALS) decreased the mortality of severe trauma patients transferred to the trauma centre (mainly from rural areas) but had no measurable effect on disability or quality of life of trauma survivors. 4. ALS in the pre-hospital setting did not have a measurable benefit in mortality, disability or the quality of life of severe trauma patients directly admitted to the trauma centre. 5. Trauma related disabilities and compromises in quality of life are still important at 6 months after injury. MAIN RECOMMENDATIONS 1. Special attention should be paid to prevention. To decrease deaths at the incident scene injury prevention initiatives are the most important ones as deaths happening at the scene are inevitable. 2. The development of an effective trauma system and EMS is paramount. To reduce the second peak of death there must be continuous and articulated effort to support key issues in the chain of treatment, namely: the development of pre-hospital EMS and in-hospital emergency care; the development of trauma teams and trauma education in general; efforts on trauma system development to improve initial stabilization and expedite pathways of transfer to definitive care. 3. Special attention should be drawn to ICU availability and treatment of severe head injury. Concerning the 2 days peak of mortality, ICU treatment is of paramount importance because mortality is increased due to severe head injury and aging of the population. In the last decades we observed enormous advances in resuscitation strategies, acceptance of damage control and improvement in diagnostic technology. Now we must put more effort into researching the optimal management of head injuries and old patients in the ICU environment. That recommendation is also important to deal with the latest 2 weeks peak of mortality (12%), important to prevent infection and multiple organ dysfunctions. 4. The pre-hospital design of trauma systems and EMS should keep the ALS medically based team mainly in areas to whom the trauma centre is a long distance or more than one hour away. The pre-hospital presence of an ALS team that is able to deal with life threatening events improves transferred patient mortality even if this prolongs time spent to reach the trauma centre. 5. It is paramount to establish patient, family and society awareness about the burden of trauma. Rehabilitation strategies that link the other elements of the trauma system would be essential to close the loop of care for trauma patients along with a well designed system to facilitate a social, familiar and employment (when applicable) integration in society. 6. The recommendations described above are impossible to accomplish without the development of a national trauma registry.